Uma análise da parceria público-privada na gestão hospitalar: um estudo de caso na perspectiva dos estudos em ciência, tecnologia e sociedade - Silva, Meliza Cristina da (2010)
The increasing technological change and intense health service, which provides worldwide, brings as a consequence the necessity of development and incorporation of new models of management and financing. These managerial innovations include a look at private institutions, to the establishment of strategies such as PPP - Public Private Partnership model in the SHO - the Social Health Organizations. This study presents an analysis of the adoption of strategies of the PPP in hospital management from the perspective of studies STS - Science, Technology and Society. The objective was to analyze the process of managing the Bauru State Hospital - BSH, scrutinizing its construction, operation strategies and the results of the PPP. The method adopted in this investigation is the case study and bibliographical review on the STS subject, the PPP and the SHO. The result of the thesis demonstrates the range and often overcoming the qualitative and quantitative goals of the Health Secretariat of São Paulo in the PPP of BSH, from its creation to the updating of the procurement and management over the seven years of partnership. PPP's strategy has enabled the provision of services to the region of Bauru once concentrated in towns. This dissertation is the proposal to incorporate discussions on PPP in hospital management to field studies STS.